The Reception of Biblical Figures - Hamidović, David; Serra, Eleonora; Therrien, Philippe (Brepols, 2024)
This volume explores the reception of biblical figures in Judaism, Christianity and Islam, with a particular focus on Antiquity and incursions in the Middle Ages and modernity. The contributions included here offer a glimpse of the complexity of the mechanics of transmission to which these figures were subjected in extra-biblical texts, either concentrating on one author or corpus in particular, or broadening the scope across time and cultural contexts. The volume intends to shed light on how these biblical figures and their legacies appear as channels of collective memory and identity; how they became tools for authors to achieve specific goals; how they gained new and powerful authority for communities; and how they transcend traditions and cultural boundaries. As a result, the vitality and fluidity of the developments of traditions become clear and prompt caution when using modern categories.